Voices in the Media performing French linguistic otherness - Planchenault, Gaëlle (Advances in sociolinguistics series, 2017)
"Verbal performances are often encountered in the media where they are used to embody characters or social archetypes. Performed voices define the norm as well as the linguistic Others and by doing so circulate associated values and linguistic ideologies. This book explores the idea that, far from simply being exercises in verbal skill and flair, performances of social, ethnic or gendered voices in the media not only have the power to accomplish ideological work, they are also sites of linguistic tension and negotiation.Critically examining performances of French voices in the media, this book raises the following questions:- How are repertoires of voices constructed and subsequently perpetuated in the media? - How do the stereotypic personae these voices contribute to build become familiar to national as well as transnational audiences? - How do such performed voices reproduce hegemonic ideologies of standard and non-standard languages and participate in the perpetuation of social discriminations? - How are these performed voices commodified into cultural products of otherness that may later be reclaimed by stigmatized communities? Following an innovative framework which allows for analysis of performances of varied voices and their impact in the media sphere, Voices in the Media offers a new approach to the linguistics of media performance"--Provided by publisher.